The Influence of supply chain management dimensions on the performance of electric cable companies in Jakarta - Khoe, Marika; Rakhman, Abdullah (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2023)
A good and effective company supply chain determined around 60% of the company's sustainability. In detail, strategic supplier partnerships, customer relationships, information sharing, and information quality positively affect company performance. To investigate this notion, the authors conducted the study in an electric cable company in Jakarta among stakeholders who had lived in Jakarta for the past six months chosen by the census. The results show that strategic supplier partnership, information sharing, and information quality affect company performance. The most influential variable on the company's performance is information sharing. Customer relationship shows a positive but not significant effect on company performance. The research found that strategic supplier partnerships, customer relationships, information sharing, and information quality can explain the variance in company performance of 63.2%.